Estrategias didácticas y su aporte en el aprendizaje de los niños en la etapa inicial de la Unidad Educativa Francisco Huerta Rendón del cantón Babahoyo, Provincia de Los Ríos - Avilés Medrano, Jennifer Elena (2022)
One of the rights that children have is the abscess to School Education, taking into account that teaching in the initial stage is the basis of their development for life, and Knowing that learning is changing over time, it carries a great responsibility in the development of children, which is why this research of didactic strategies for children of initial stage is carried out, knowing that children in their development not only they need basic study such as reading and writing, children revolve around the game, they need to interact, relate, give them the necessary values to live in society, giving them active participation in the teachings. The teacher plays the fundamental role in the teaching process, leads to planning, putting into practice and evaluating, and thus achieving significant learning in children, in other words, planning the use of necessary teaching material. To carry out this Case Study, information was obtained through interview, observation and research, the content on the use of didactic materials was analyzed from a large amount of information consulted in research texts, a method was used, based on field research, to observe, analyze, examine directly and arrive at possible investigations that facilitate better learning.